KNOWLEDGE SHARING IN RICE RESEARCH. 3. CITATION ANALYSIS OF IRRI SCIENTISTS' LITERATURE OUTPUT, 2000-2004 - Ramos, Mila M.; Austria, Carmelita S.; delos Reyes, Natalia; Laxamana, Emerald; Austria, Reagan; Parducho, Ma. Consuelo (Journal of Philippine Librarianship; Vol 27, No 1&2 (2007), 2008)
The paper looks at scholarly works of IRRI scientists published in the journals to determine which among the scholarly works of the scientists have the most impact based on the frequency of usage by other scientists. Some of the findings of the study are as follows: a) IRRI scientists prefer to submit their papers to peer-reviewed journals, b) national journals are not cited as frequently, c) Google Scholar reports more citations than Scopus or Web of Science and d) citations of IRRI publications are on the uptrend. It includes an appendix that shows the Highly Cited IRRI journal publications from 2000 to 2004.
Keywords: International Rice Research Institute, Citation analysis, IRRI Journals, IRRI publications